2017
DOI: 10.1002/ird.2180
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Using Drainage Water of Fish Farms for Irrigation: Field and Modelling Study Using the SALTMED Model

Abstract: This study investigated the suitability and benefits of using drainage water of fish farms (DWFF), instead of canal fresh water (IW), for wheat irrigation. Two water qualities, DWFF and IW, and four levels of N‐fertigation rates [100% N (192 kg N ha−1 season−1), 80% N, 60% N and 40% N] were tested. The results showed a positive impact when increasing N‐fertigation rate on the yield using both DWFF and IW. However, the yield under DWFF was higher than the yield under the IW treatment by between 11 and 51% in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…These findings may be due to the additional amount of dissolved biological nitrogen and other nutrients inherent in waste water of fish farm. These results are in accordance with those obtained by Abdelraouf and Ragab (2017) how found that the yield under waste water of fish farm was higher than the yield under well ground water.…”
Section: Stalk Length and Diameter (Cm)supporting
confidence: 93%
See 1 more Smart Citation
“…These findings may be due to the additional amount of dissolved biological nitrogen and other nutrients inherent in waste water of fish farm. These results are in accordance with those obtained by Abdelraouf and Ragab (2017) how found that the yield under waste water of fish farm was higher than the yield under well ground water.…”
Section: Stalk Length and Diameter (Cm)supporting
confidence: 93%
“…A Reuse waste water of fish farming as a new resource for irrigation and rich with organic matter can improve soil quality and crops productivity and reduce the total costs of fertilizers by adding minimum doses from mineral fertilizers and reduce the pollution in soil. Abdelraouf and Ragab (2017) found that the yield under waste water of fish farm (WWFF) was higher than the yield under the canal fresh water (IW) by 11 and 51% in 2014 and 8 and 38% in 2015 seasons.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with these obtained by (Elnwishy et al, 2006) who stated that, recycling the drainage water of fish farming, rich with organic matter for agriculture use can improve soil quality and crops productivity. In addition, Abdelraouf and Ragab (2017) found that the yield under waste water of fish farm was higher than the yield under well ground water. On the other hand, Gibberellic acid has the ability of effect on yield by modifying the growth pattern by affecting the cell elongation and cell division, biosynthesis of enzymes, protein, and carbohydrates contents (Gupta andChakrabarty, 2013 andMilne et al, 2013).…”
Section: Yieldsmentioning
confidence: 99%
“…The study results reveal that watering with fishpond water for almost two decades has positively affected grape yields compared to irrigating with just ditchwater (Figure 2), which is consistent with similar studies from other locations and systems. In different studies, fishpond water increased paddy rice [21,22,28] and wheat [29] yields. The positive yield effects from fishponds relate to soil fertility and health improvements, as observed by others [28,29], which is also consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 98%